3137 fetuses in 33 years: What we have learned from the Wisconsin stillbirth service program. Issue 9 (25th February 2021) - McPherson, Elizabeth W.
Abstract: The Wisconsin Stillbirth Service Program (WiSSP) provided expert review by a dysmorphologist for community‐acquired data on 3137 fetal deaths between 1983 and 2017. Intrinsic fetal causes were consistently identified in about 25% while placental and maternal causes were recognized with increasing frequency as attention was shifted from a primarily fetal to a multifocal approach. Identification of causes increased from 40% to 78% and in about half of cases results of the review altered recurrence risk and/or future pregnancy management. Banked data from WiSSP formed the basis of 24 publications, more than half of which have a genetic counselor and/or summer premedical student intern as an author. The earlier publications emphasized validation of the concept of community‐based evaluation with central review, the utility of various parts of the WiSSP protocol, the similarity of second‐trimester miscarriages <20 weeks to later stillbirths with respect to causes identified and recurrence risks, and the potential for results of etiologic evaluation to influence future prenatal care. The most important recurrent theme, however, was the interaction of intrinsic fetal, placental, and maternal factors in contributing to fetal demise. This implies that, at least in developed nations with available obstetric care, reduction in stillbirth will require careful attention to the myriad of factors contributing to fetal, placental, and maternal well‐being.